Advanced glycation end products augment experimental hepatic fibrosis. Issue 2 (22nd January 2013) - Goodwin, Michelle; Herath, Chandana; Jia, Zhiyuan; Leung, Chris; Coughlan, Melinda T; Forbes, Josephine; Angus, Peter
Abstract Background and Aims Advanced glycation end products (AGEs) are nonenzymatic modifications of proteins by reducing sugars. These compounds accumulate in a number of chronic disease states, contributing to tissue injury via several mechanisms, including activation of the receptor for advanced glycation end products (RAGE). We aimed to investigate whether AGEs can exacerbate chronic liver injury and contribute to hepatic fibrosis. Methods We initially studied the effects of chronic hepatic exposure to high levels of AGEs given intraperitoneally as AGE‐rat serum albumin. In a separate experiment, we examined the impact of high AGE exposure in rats following bile duct ligation (BDL). Results In normal rats, chronic AGE‐rat serum albumin administration induced significant increases in α‐smooth muscle actin gene and protein expression but did not induce fibrosis or biochemical evidence of liver injury. However, in BDL animals, AGE‐bovine serum albumin administration significantly increased hepatic fibrosis as evidenced by increased collagen content and α‐smooth muscle actin expression, compared with BDL alone. Furthermore, AGEs increased hepatic oxidative stress and receptor for advanced glycation end products gene expression. Conclusions These findings suggest that AGEs may contribute to the pathogenesis of chronic liver injury and fibrosis.